Application of Fuzzy Analytical Hierarchy Process for Revising OIU Main-Campus Masterplan to Ensure Sustainable Environment - Elsadig E.H.O.; Abdalla G.M.T.; Eltahir M.M.; Hayder G.; Lakhouit A.; Abdel-Magid I.M.; Abdel-Magid H.I.; Messaoud A.B.; Yasin A.H.A.; Sayed O.A.; Elsawi M.B. (Springer Nature, 2024)
Omdurman Islamic University is one of the oldest universities in Sudan. OIU campus masterplan (CMP) was first developed in 1978 and revised in 2002. Yet too many important parts of the revised CMP need to be redesigned and constructed. Revising the existing university masterplan is complicated and needs to be tackled carefully in the light of new conceptual criteria without affecting the ongoing educational, research, and administrative activities. Furthermore, for the sustainability of the facilities to be increased, there are key approaches, namely, environmental-friendly materials, environmental-friendly landscape, safety, conservation of energy, and extended operation life. The Fuzzy Analytical Hierarchy Process (FAHP) is to solve multi-level and complex decision-making problems in a systematic approach. Based on experts judgment on several design alternatives and criteria in addition to sub-criteria. The opinions are compared in a pairwise fashion based on three expertise and three decision-makers as the criteria and sub-criteria to assess how their contribution to the target. This paper aims at building a new assessment framework for sustainable CMP to be later applied to the case study of OIU main campus in Sudan. To assess the proposed CMP in terms of sustainability, three sustainable alternatives (A1, A2, and A3) are proposed, along with four criteria and 13 sub criteria (factors). The alternatives are studied for the best alternative selection. Each of the criterion and factor weight is calculated using the FAHP. The analysis result shown a rational procedure which utilizes successfully the use of FAHP to help the decision processes for the OIU revised CMP. 2023, The Author(s), under exclusive license to Springer Nature Switzerland AG.